Hubungan Tingkat Pengetahuan Dan Sikap Terhadap Perilaku Pencegahan Hepatitis B Pada Mahasiswa Fakultas Kedokteran Universitas Kristen Duta Wacana Angkatan 2019 Dan 2020 - Trixie Alfreda, Agnes; Ardiyan, Yustina Nuke; Dimasto Kristiyanto, Haryo; Marlene Sooai , Christiane (Syntax Corporation, 2025)
Background: Hepatitis B is an inflammatory liver disease caused by both infectious and non-infectious causes, with Hepatitis B being a global concern. The WHO estimates 820,000 deaths from Hepatitis B in 2019, with 1.5 million new infections occurring annually. Indonesia has the highest mortality rate, at 2.14 per 100,000 population. Medical students, as future healthcare workers, are at risk of exposure to infectious diseases such as Hepatitis B, so their understanding of and attitudes toward infection prevention are crucial. Objective: The purpose of this study was to determine the relationship between knowledge and attitudes toward Hepatitis B prevention behavior among students of the Faculty of Medicine, Duta Wacana Christian University, intakes of 2019 and 2020. Methods: This study used an observational analytical design and a cross-sectional study. Results: This study involved 61 respondents. Analysis using Spearman correlation test shows correlation coefficient (r) between knowledge and attitude of -0.309 and -0.296 respectively, with significance value (p) of 0.016 and 0.021. Conclusion: The level of students' knowledge of Hepatitis B is classified as good, with an average percentage of answers above 75% and a significance value (p) of 0.016. There is a significant relationship between attitudes and preventive behavior as evidenced by a significance value (p) of 0.021. Knowledge and attitudes towards Hepatitis B preventive behavior also show a significant relationship with significance values (p) of 0.016 and 0.021 respectively.